2023
DOI: 10.47626/2237-6089-2021-0429
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectionality of smoking and depression in adolescents: a systematic review

Abstract: ObjectiveRecently, there is an increase in evidence that both smoking and mental health are continuously increasing among adolescents. This systematic review elucidates the research on evidence of the direction of association and risk factors influencing this relationship between smoking and depression. We also highlight the recent studies on the effects of electronic cigarettes and the development of the association between depression and smoking. MethodA literature search was conducted on databases including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…Mental health problems and substance use also affect each other [ 31 ], increasing the risk of co-occurrence, and the prognosis is worse for comorbidities [ 32 ]. Although there is still no consensus as to whether depression increases substance consumption or whether substance consumption increases depression, evidence that depression precedes substance consumption is stronger, and longitudinal studies have shown this [ 28 , 33 ]. In addition, while loneliness and depression have different definitions, low social skills and a negative impact on interpersonal relationships are common to both; they are not only closely related but often occur simultaneously [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mental health problems and substance use also affect each other [ 31 ], increasing the risk of co-occurrence, and the prognosis is worse for comorbidities [ 32 ]. Although there is still no consensus as to whether depression increases substance consumption or whether substance consumption increases depression, evidence that depression precedes substance consumption is stronger, and longitudinal studies have shown this [ 28 , 33 ]. In addition, while loneliness and depression have different definitions, low social skills and a negative impact on interpersonal relationships are common to both; they are not only closely related but often occur simultaneously [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking and cannabis use are both prospectively associated with increased risk of depression in conventional observational studies [4][5][6][7][8][9][10]. These substances are commonly coused, a behaviour comprising 'concurrent use' (i.e., use of both products in a pre-defined time period, including 'sequential' use) and co-administration (i.e., used simultaneously via the same delivery method) [11], the latter of which is more common in European countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, approximately 1.14 billion adults globally had smoked tobacco regularly and an estimated 200 million people used cannabis in the last year. 1 Existing observational evidence demonstrates prospective associations between cannabis use, tobacco use and mental ill-health; including depression, [2][3][4][5][6][7][8][9][10][11][12] anxiety, [7][8][9][10][12][13][14][15][16] and psychosis. 10,[17][18][19][20][21][22][23][24][25][26] However, it remains unclear if the associations in question are causal or if they result from observational data biases (e.g., confounding, reverse causality).…”
Section: Introductionmentioning
confidence: 99%